Analisis tentang Konsekwensi Yuridis Harta Bersama terhadap Kewajiban Suami Memberi Nafkah dalam KHI - Syuhada' Syuhada' (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2013)
Compilation of Islamic Law (KHI) has determined that the obligation imposed on husbands make a living, which is contained in Article 80 paragraph (4). In addition to these provisions, also set provisions regarding joint property. According to article 1 letter f KHI that community property is property acquired either individually or together with the spouses during the marriage takes place, regardless registered to anyone. Consequences arising from the joint property of the deeds of the law of property should be agreed with both parties and the division ofproperty is done in a balanced way. If the provisions regarding joint property associated with the obligation of the husband to provide for the legal issues can come up when the wife did claim that a given property during the marriage as a living interpreted as joint property.Then the rule also shows unfair to the husband because in addition he is obligated to provide for he is also bound by the provisions of that division of property jointly conducted fairly. Three juridical consequences joint property of the husband to provide for an obligation that is optional. First, husband and wife shared responsibility in the family economy. Second, the separation of conjugal property in marriage. Third, compromise joint property and liability rules provide for her h usband.